Paralyzing the WTO from the Inside: The Deadlock of the Appointment of Appellate Body Judges and its Repercussions - I Gusti Ngurah Parikesit Widiatedja; Mohammad Qadam Shah (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
The establishment of the dispute settlement procedure that consists of the Panel Report and the Appellate Body has been the most remarkable characteristic of the World Trade Organization. Beside the most productive international dispute resolution process, it has consistently adopted a rule-oriented procedure in enforcing the commitments made during trade negotiations. Since the last five years, however, the dispute settlement process has confronted an existential crisis. While conflict resolution through consultations and panels continues, the process under the Appellate Body is forced to stop. The United States has impaired the appointment of additional judges to this body, preventing it from obtaining the quorum required to hear appeals. By employing a normative research, this paper aims to identify and analyze the deadlock of the appointment of the Appellate Body judges and its repercussions for international trade governance, including Indonesia. This deadlock could jeopardy the viability of global trading system as there would be no proceeding to hear the dispute at the appellate level. Some cases that involved Indonesia would also be affected, particularly if the parties are willing to continue this process to the Appellate Body.